HUBUNGAN PEMBERIAN AIR SUSU IBU (ASI) EKSKLUSIF DENGAN KEJADIAN BRONKIOLITIS PADA BAYI USIA 7-24 BULAN - Rina Wahyuningsih; Yuni Sufyanti Arief; Ilya Krisnana (Universitas Airlangga, 2019)
Introduction: Bronchiolitis is a viral lower respiratory tract infection characterized by bronchial inflamation. Generally, the infection is caused by respiratory syncytial virus (RSV). Bronchiolitis is caused by several factors, one of which is exclusive breastfeeding. This research was conducted to know the correlation between exclusive breastfeeding and bronchilitis cases at RSUD Soemarno Sosroatmodjo, Bulungan, North Kalimantan.Method: The design of this research was descriptive analysis with cross-sectional approach. The population of this research was 7-24 month old babies suffered from bronchiolitis at RSUD Soemarno Sosroatmodjo with 32 babies as the samples. Sampling techninique used was non-probability sampling (consecutive). The independent variable in this research was giving exclusive breastfeeding, while the dependent variable was bronchiolitis case. The data were collected by using structured observation sheets and questionnaires, and then analyzed by using chi square.Result: The result of this research showed that giving exclusive breastfeeding had a correlation with bronchiolitis cases. Giving non exclusive breastfeeding correlated with acute bronchiolitis cases from mostly 32 respondents who suffered from acute bronchiolitis and had non exclusive breastfeeding with number of chi square analysis p=0.00.Conclusions: This result proved that giving exclusive breastfeeding could minimize the percentage and prevalence rate of bronchiolitis in infants. New mothers who have just given birth were suggested to give exclusive breastfeeding to their babies for 6 months